BEA MASUK IMPOR TINJAUAN HUKUM ISLAM DAN UU NOMOR 17 TAHUN 2006 TENTANG PERUBAHAN ATAS UU NOMOR 10 TAHUN 1995 TENTANG KEPABEANAN - Bachtiar, Moch Yusuf (Jurisdictie: Jurnal Hukum dan Syariah, 2014)
Import duty is one kind of new charges and under the authority of the Directorate General of Customs and Excise and has a very large share of both the income and state revenues from the domestic industry protection against attacks from abroad industry. Basic Law of Import Duty is under Article 12 of Law no. 10, 1995 On Customs which then made changes as stipulated in Law no. 17 of 2006 on the Amendment Law. 10, 1995 On Customs. In Civilization and Islamic Khazanah itself besides Zakat, Kharaj and Jizya as a form of tax on the community there is also some kind of import duty that begins with a varied amount kaafir Harbi to levy 1/10, dhimmi 2/10, and Muslim 4/10. However occurred Pros and Cons imposition of import duty on Muslims. The focus of research is on the Import Duties Law Indonesia terms of Islamic law. This research aimed to find out whether the determination of levies import duties today in accordance with the policy of the caliphate. If the same is made the same and what is different if what makes it different. This research uses the research literature by using the approach of laws and concepts and approaches using content analysis. This study concluded that the determination of levies import duty on Indonesia is in accordance with the concept of 'usyr in Islamic law and that makes it different is the use religon Islamic caliphate state while using the Indonesian nation-state.Bea masuk import merupakan salah satu jenis pungutan yang ada dan di bawah kewenangan Direktorat Jenderal bead an cukai dan mempunyai andil yang sangat besar, baik terhadap pemasukan pendapatan Negara maupun perlindungan terhadap industry negeri dari serangan industry dari luar negeri. Dasar hukum pungutan bea masuk impor diatur dalam pasal 12 UU No 10 tahun 1995 tentang kepabeanan yang kemudian dilakukan perubahan sebagaimana yang diatur dalam UU No 17 tahun 2006 tentang perubahan UU No 10 tahun 1995 tentang kepabeanan. Penelitian ini focus pada hukum bea masuk impor di Indonesia ditinjau dari segi hukum islam. Penelitian ini ditujukan untuk mengetahui apakah penetapan pungutan bea masuk import saat ini juga sesuai dengan kebijakan pada masa kekhalifahan, jika sama apa kesamaannya dan jika berbeda apa perbedaannya. Penelitian ini menggunakan jenis penelitian kepustakaan dengan menggunakan penggunaan Undang-undang dan pendekatan konsep dan menggunakan analisa konten. Kesimpulannya adalah bahwa penetapan adanya pungutan bea masuk impor di Indonesia adalah sesuai dengan konsep ‘usyr dalam hukum Islam menggunakan religion state, sedangkan Indonesia menggunakan natin state.